P01.014 Spatial correlation of FET uptake and MRI contrast enhancement in newly diagnosed glioblastoma patients prior to treatment. (19th September 2018) - Lohmann, P; Stavrinou, P; Lipke, K; Bauer, E K; Ceccon, G; Werner, J; Fink, G R; Shah, N J; Langen, K; Galldiks, N
Abstract: Background: A complete glioma resection is known to prolong survival. Contrast enhancement (CE) in MRI is usually the target for resection but the solid tumor mass may extend beyond the area of CE. It has been demonstrated that amino acid PET can detect tumor parts showing no CE in MRI. We systematically investigated the volumetric correlation of amino acid uptake with PET and CE in MRI in newly diagnosed and untreated glioblastoma patients. Material and Methods: Preoperatively, 26 patients were examined by O-(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) PET and contrast-enhanced MRI. Enhancing tumor areas on MRI were manually segmented on each transverse section and the sum of the areas was multiplied by the slice thickness to obtain contrast-enhancing volumes. The calculation of FET PET tumor volumes was based on an auto-contouring process using a tumor-to-brain ratio of 1.6 or more. For volumetric comparison, the Dice and Jaccard spatial similarity coefficients (DSC; JSC) and the percentage of overlapping volumes (OV) were calculated. Postoperatively, a glioblastoma was confirmed neuropathologically in all patients. Results: FET PET tumor volumes were significantly larger than contrast-enhancing volumes (26.7 ± 13.4 mL vs. 15.1 ± 11.5 mL; P =0.002). The spatial similarity between FET PET and CE was poor (mean DSC, 0.44 ± 0.18; mean JSC, 0.30 ± 0.14). Additionally, approximately one quarter of patients (n=7) showed a low spatial overlap (mean OV, 36 ± 18%). Conclusion: The present data suggest that the metabolic tumor volume as detected by FET PET is substantially underestimated by CE. Information derived from both imaging modalities should be integrated for the routine management of patients with newly diagnosed glioblastoma.